1991
DOI: 10.1111/j.1365-3083.1991.tb02546.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG Subclasses in Bronchoalveolar Lavage Fluid from Patients with Asthma

Abstract: We have measured Immunoglobulin G (IgG) subclasses in serum and bronchoalveolar lavage fluid (BALF) from 12 non-smoking patients with stable asthma and 9 non-smoking healthy volunteers to obtain information on their possible role in local immunological reactions. The quotients (concentration of IgG subclass in BALF)/(concentration of IgG subclass in serum) were calculated. In controls QIgG3 were lower than QIgG1, QIgG2 and QIgG4. The IgG subclasses in BALF and epithelial lining fluid (ELF) from patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…Taken together with the fact that inhaled allergens can be contaminated with endotoxins, these 2 signals could augment Th2 inflammation in the lung during secondary responses (19). Intriguingly, this hypothesis is supported by clinical studies that have shown increased IgG levels in the bronchoalveolar lavage (BAL) of patients with asthma due to increased leakage from the blood as well as increased local IgG production (20,21). Furthermore, other studies have identified allergen-specific ICs in the sera of allergic individuals (22).…”
Section: Introductionsupporting
confidence: 50%
“…Taken together with the fact that inhaled allergens can be contaminated with endotoxins, these 2 signals could augment Th2 inflammation in the lung during secondary responses (19). Intriguingly, this hypothesis is supported by clinical studies that have shown increased IgG levels in the bronchoalveolar lavage (BAL) of patients with asthma due to increased leakage from the blood as well as increased local IgG production (20,21). Furthermore, other studies have identified allergen-specific ICs in the sera of allergic individuals (22).…”
Section: Introductionsupporting
confidence: 50%
“…There was an increase in IgG-1 and to a lesser extent in IgG-3 in asthmatic patients (Group A). This is in contrast to the findings of Out et al, 9 who found IgG-3 levels lower in BALF of healthy adults compared to their serum concentrations of IgG-3. We have no explanation why IgG-3 levels in that particular study were not increased, since it is well known that IgG-1 and IgG-3 are regulated together.…”
Section: Discussioncontrasting
confidence: 85%
“…27 These differences are probably due to the chronic inflammation at the mucosal level in asthmatic patients, whereas nonasthmatic patients with recurrent infections were examined during infection-free periods; we do not have an explanation for their higher concentrations of IgG-1. Out et al 9 proposed that delayed plasma transudation of IgG-3 was due to its higher molecular mass and shorter half-life compared to the other IgG-subclasses. This led to lower levels of IgG-3 in BALF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While IgE levels can be extremely elevated in asthma, the majority of subjects with asthma has serum immunoglobulin levels (including IgE) within the normal range and lacks other symptoms consistent with immunodeficiency [1]. Also, immunoglobulin levels in bronchoalveolar lavage (BAL) or airway lining fluid have been reported to be increased, as would be expected for an ongoing airway inflammatory process [3, 4]. Only a fraction of severe asthmatics have serum immunoglobulins (most often IgG) below normal levels, and this reduction has generally been attributed to steroid therapy [5, 6].…”
Section: Introductionmentioning
confidence: 99%